Platform for Teaching Speaking Skills Online in the Pandemic Era - Dwijaksara, Ni Kadek Diah Widyastuti (Universitas Pendidikan Ganesha, 2021)
Educators were faced with the unexpected difficulty of primarily teaching online. Many challenges arose as a result of the necessity to redesign instructional activities, including inconsistency, challenging time management, maintaining students' interest, and increasing cheating in online tests. Because of the COVID-19 epidemic, the Indonesian government has implemented policies in the school sector. Previously, the teaching and learning process, particularly in higher education, was conducted face to face, and it has now transitioned to entirely online learning. This scenario requires the teachers and students to use online learning, which has an impact on their learning experiences. Speaking skill is very essential for human beings in, with an order to be able to communicate with society. During the pandemic era, teachers and students face difficulties to study because of lockdown in some areas. Here, the platforms categorized as Vacaroo, Voki, Fotobubble, and VoiceThread for learning speaking in a fun way, and cherish.